Preparation method of chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film

Through Fe3+ chelated chitosan and gallic acid cross-linking technology, the problem of insufficient mechanical strength and UV resistance of traditional chitosan films is solved, and a high-strength, antioxidant, recyclable composite film is prepared, with excellent UV resistance.

CN119505311APending Publication Date: 2025-02-25JILIN TEACHERS INST OF ENG & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411673032.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional chitosan films have poor mechanical strength, poor thermal stability and poor UV resistance.

Method used

Fe3+ chelated chitosan and gallic acid were used to form a high-strength flexible composite film through hydrogen bonding and Fe3+ chelation cross-linking.

Benefits of technology

The prepared composite film has high efficiency and anti-UV effect, strong mechanical properties, suitable for covering various shapes, recyclable use, and can maintain 100% anti-UV performance for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505311A_ABST
    Figure CN119505311A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film, and belongs to the field of functional materials. According to the specific scheme, the method comprises the following steps: 1, dissolving chitosan in an acetic acid solution to obtain a solution A; dissolving gallic acid in an ethanol solution to obtain a solution B, and dissolving a salt containing Fe < 3 + > in deionized water to obtain a solution C; and 2, uniformly mixing the solution A and the solution B, heating, uniformly mixing with the solution C, heating, cooling to room temperature, pouring into a mold, and drying to obtain the chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film. The prepared chitosan-based high-strength composite film has an efficient anti-ultraviolet function, the anti-ultraviolet efficiency can reach 100%, the long-time anti-ultraviolet function can be kept, and 100% anti-ultraviolet efficiency can still be kept after long-time ultraviolet irradiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, and in particular relates to a method for preparing a chitosan-based (CS) high-strength anti-ultraviolet and anti-oxidation composite film. Background Art

[0002] Chitosan (CS) is a unique natural polysaccharide known for its excellent biocompatibility and biodegradability. It has good antibacterial properties and can effectively inhibit the growth of a variety of bacteria, so it is widely used in food preservation and medical fields. At the same time, chitosan can also form tough and transparent films, which are suitable for food packaging and agricultural preservation. Its cationic properties further expand the scope of application and can play an important role in water treatment and drug delivery. These comprehensive characteristics make chitosan a valuable material in many industries.

[0003] Gallic acid is a natural phenolic compound that is widely found in plants, especially tea, grapes and certain fruits. It has good antioxidant properties and can effectively neutralize free radicals, thereby combating oxidative damage to cells. In addition, gallic acid also exhibits antibacterial properties, can inhibit the growth of a variety of pathogenic microorganisms, and has a certain anti-inflammatory effect. At the same time, gallic acid is widely used in food, cosmetics, medicine and other fields. Its safety and biocompatibility make it an ideal natural additive. These unique characteristics make gallic acid have a wide range of application potential in the fields of health care and beauty.

[0004] The prior art discloses a pure chitosan film and a preparation method thereof, wherein the film prepared by using chitosan (CS) has the characteristics of good biodegradability, air permeability, and good film-forming property. However, the film prepared by this method has the disadvantages of poor mechanical strength, poor water resistance, poor thermal stability, etc. Summary of the invention

[0005] In order to solve the shortcomings of traditional chitosan (CS) films such as poor mechanical strength, poor thermal stability, and poor UV resistance, the present invention provides a Fe 3+ A method for preparing a high-strength anti-ultraviolet and anti-oxidation composite film of chelated chitosan and gallic acid. The preparation method is non-toxic and harmless, and the experimental operation is simple and convenient, and it is convenient to use at any time. The prepared composite film has the advantages of high-efficiency anti-ultraviolet effect, strong mechanical properties, suitable for covering various shapes, and can be recycled. It is determined to be 100% anti-ultraviolet, and the anti-ultraviolet performance can be maintained for a long time.

[0006] In order to achieve the above technical objectives, the specific technical solutions are as follows:

[0007] A method for preparing a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film comprises the following steps:

[0008] Step 1: Dissolve chitosan in acetic acid solution to obtain solution A; dissolve gallic acid in ethanol solution to obtain solution B; 3+ The salt is dissolved in deionized water to obtain solution C;

[0009] Step 2: Mix solution A and solution B evenly and heat them, then mix them evenly with solution C and heat them, cool to room temperature, pour into a mold, and obtain a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film after drying.

[0010] In step 1, the concentration of chitosan in the solution A is 0.5-3 g / 100 mL, and the mass fraction of the acetic acid solution is 0.5-3%.

[0011] In step 1, the concentration of gallic acid in the solution B is 0.1-0.3 mol / 100 mL, and the mass fraction of the ethanol solution is 30%-80%.

[0012] In step 1, the Fe 3+ The concentration is 0.5-1.5mg / mL.

[0013] In step 1, the Fe 3+ The salt includes one or more combinations of FeCl3, Fe2(SO4)3, and Fe(NO3)3.

[0014] In step 2, the volume ratio of solution A, solution B and solution C is 20:2:1.

[0015] In step 1, chitosan and acetic acid solution are mixed, heated to 30-50°C, and magnetically stirred for 0.2-0.8h until completely dissolved; gallic acid and ethanol solution are mixed, and magnetically stirred at 50-80°C for 0.5-1.5h until completely dissolved; Fe 3+ The salt was mixed with deionized water, ultrasonicated, and magnetically stirred at 30-50 °C for 0.1-0.5 h until completely dissolved.

[0016] In step 2, the solution A and solution B are mixed and then heated at 50-70° C., and the solution A, solution B and solution C are mixed and then heated at 60-85° C.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) Chitosan, gallic acid and Fe 3+ Ions through hydrogen bonds, Fe 3+The selected chitosan, gallic acid and iron salt are all abundant, readily available and non-toxic materials. The hydrogen bond interaction between chitosan and gallic acid makes the prepared film have better flexibility and strength than pure chitosan film. 3+ The chelation with chitosan and gallic acid further strengthens the network structure of the film, making the film have antioxidant properties. This composite film with high-strength anti-ultraviolet properties can be used in various occasions to resist ultraviolet radiation. It is simple to prepare, can run quickly, has high strength, does not hydrolyze, and has high anti-ultraviolet efficiency. It is a film material with excellent performance.

[0019] (2) The chitosan-based high-strength composite film prepared by the present invention has a highly efficient anti-ultraviolet function, the anti-ultraviolet efficiency can reach 100%, and can maintain a long-term anti-ultraviolet function, and can still maintain 100% anti-ultraviolet efficiency after long-term ultraviolet irradiation.

[0020] (3) The process of preparing the chitosan-based high-strength composite film of the present invention does not require the use of strong alkali or strong acid such as sodium hydroxide or concentrated sulfuric acid for adjustment, thereby reducing the amount of chemical agents used and achieving the stability of the film under mild conditions.

[0021] (4) The film prepared by the present invention has anti-oxidation and certain hydrophobic functions, and can therefore be recycled without destroying the morphology of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Fe 3+ Schematic diagram of the preparation method of chelated chitosan (CS) and gallic acid (GA) high-strength anti-ultraviolet and anti-oxidation composite film;

[0023] Figure 2 Fe 3+ SEM images of the network structure of the chelated chitosan (CS) and gallic acid (GA) high-strength UV-resistant and antioxidant composite films;

[0024] Figure 3 Fe 3+ Tensile test diagram of high-strength UV-resistant and antioxidant composite film of chelated chitosan (CS) and gallic acid (GA);

[0025] Figure 4 (a) and (b) are Fe 3+ Ultraviolet absorption test and light transmittance test diagram of chelated chitosan (CS) and gallic acid (GA) high-strength anti-ultraviolet and anti-oxidation composite film;

[0026] Figure 5 Fe 3+Antioxidant test diagram of chelated chitosan (CS) and gallic acid (GA) high-strength anti-ultraviolet and anti-oxidant composite film;

[0027] Figure 6 Fe 3+ Schematic diagram of the hydrophobic angle test of the chelated chitosan (CS) and gallic acid (GA) high-strength anti-ultraviolet and anti-oxidation composite film; (a): contact angle test photo of CS film; (b): contact angle photo of CSGA-0.3 composite film; (c): contact angle photo of CSGA-1.5Fe 3+ Contact angle photos of composite films; (d): CS, CSGA-0.3, CSGA-1.5Fe 3+ Contact angle bar graph;

[0028] Figure 7 Fe 3+ Photo of the UV test card of the chelated chitosan (CS) and gallic acid (GA) high-strength UV and antioxidant composite film;

[0029] In the figure, CS represents pure chitosan film, and the concentration of CS is 1g / 100mL; CSGA represents the composite film of chitosan and gallic acid, among which CSGA-0.1 represents the CSGA composite film prepared when the concentration of chitosan is 1g / 100mL and the concentration of gallic acid is 0.1mol / 100mL; CSGA-0.2 represents the CSGA composite film prepared when the concentration of chitosan is 1g / 100mL and the concentration of gallic acid is 0.2mol / 100mL; CSGA-0.3 represents the CSGA composite film prepared when the concentration of chitosan is 1g / 100mL and the concentration of gallic acid is 0.3mol / 100mL; CSGA-0.5Fe 3+ Represents the addition of 0.5mg / mLFe to 1g / 100mL chitosan and 0.3mol / 100mL gallic acid 3+ The prepared Fe 3+ -CSGA composite film; CSGA-1.0Fe 3+ Represents the addition of 1 mg / mL Fe to 1 g / 100 mL chitosan and 0.3 mol / 100 mL gallic acid. 3+ The prepared Fe 3+ -CSGA composite film; CSGA-1.5Fe 3+ Represents the addition of 1.5mg / mLFe to 1g / 100mL chitosan and 0.3mol / 100mL gallic acid 3+ The prepared Fe 3+ -CSGA composite film; CSGA-2.5Fe 3+Represents the addition of 2.5mg / mLFe to 1g / 100mL chitosan and 0.3mol / 100mL gallic acid 3+ The prepared Fe 3+ -CSGA composite film. DETAILED DESCRIPTION

[0030] The technical solutions in the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. Unless otherwise stated, the raw materials in the embodiments of the present invention are purchased through commercial channels.

[0031] In order to solve the problem of poor toughness of pure chitosan film, the present invention proposes a green, simple and effective method of utilizing Fe 3+ A method for preparing a high-strength anti-ultraviolet and anti-oxidation composite film of chelated chitosan and gallic acid, by which a chitosan-based film with multiple three-dimensional cross-linked structures is prepared. First, a solution B containing gallic acid (GA) is added to a solution A containing chitosan (CS) with a deacetylation degree of ≥95%, and a double network structure is formed by chemical covalent bonds and hydrogen bonds. Then, metal Fe is added 3+ , Fe 3+ The metal-ligand bonds are formed with chitosan and gallic acid (GA) respectively to construct a metal-ligand-chemical covalent bond-hydrogen bond multidimensional network cross-linking system. The schematic diagram of the preparation method is shown in Figure 1 We believe that the new approach of synergistic action of metal-ligand bonds, hydrogen bonds and chemical covalent bonds is helpful for preparing high-performance chitosan-based high-strength anti-ultraviolet and anti-oxidation composite films, so that chitosan-based high-strength anti-ultraviolet and anti-oxidation films have better mechanical properties. In addition, Fe 3+ The chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film has good antibacterial properties and can be coordinated with gallic acid to form functionalized ferroferric oxide magnetic nanoparticles. 3+ (CSGA-Fe 3+ ) film has better UV resistance. This broadens its application in medicine, sensors, environmental protection, food packaging and other fields.

[0032] Example 1

[0033] A preparation method of a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film comprises the following steps: weighing 1g of chitosan (CS) into a reaction bottle, adding 100mL of 1% acetic acid solution, heating at 40°C, stirring for 0.5h to dissolve to obtain solution A. Weighing 0.01mol of GA into a reaction bottle, adding 10mL of 50% ethanol solution, stirring at 70°C for 1.0h to dissolve to obtain solution B. After mixing solution A and solution B evenly, heating at 60°C, cooling to room temperature, pouring into a mold, and drying, obtaining a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film.

[0034] Example 2

[0035] A preparation method of a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film comprises the following steps: weighing 1g of chitosan (CS) into a reaction bottle, adding 100mL of 1% acetic acid solution, heating at 40°C, stirring for 0.5h to dissolve to obtain solution A. Weighing 0.02mol of GA into a reaction bottle, adding 10mL of 50% ethanol solution, stirring at 70°C for 1.0h to dissolve to obtain solution B. After mixing solution A and solution B evenly, heating at 60°C, cooling to room temperature, pouring into a mold, and drying, obtaining a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film.

[0036] Example 3

[0037] A preparation method of a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film comprises the following steps: weighing 1g of chitosan (CS) into a reaction bottle, adding 100mL of 1% acetic acid solution, heating at 40°C, stirring for 0.5h to dissolve to obtain solution A. Weighing 0.03mol of GA into a reaction bottle, adding 10mL of 50% ethanol solution, stirring at 70°C for 1.0h to dissolve to obtain solution B. After mixing solution A and solution B evenly, heating at 60°C, cooling to room temperature, pouring into a mold, and drying, obtain a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film.

[0038] Example 4

[0039] A preparation method of a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film, comprising the following steps: weighing 1g chitosan (CS) into a reaction bottle, adding 100mL of 1% acetic acid solution, heating at 40°C and stirring for 0.5h to dissolve to obtain solution A. Weighing 0.03mol GA into a reaction bottle, adding 10mL of 50% ethanol solution, stirring at 70°C for 1.0h to dissolve to obtain solution B. Weighing 5ml of 0.5mg / mL Fe 3+Put it into a reaction bottle, add deionized water and ultrasonicate, heat at 40℃ and stir for 0.3h to dissolve to obtain solution C. Mix solution A and solution B evenly and heat at 60℃, then mix them evenly with solution C and heat at 75℃, cool to room temperature, pour into a mold and dry to obtain a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film.

[0040] Example 5

[0041] A preparation method of a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film, comprising the following steps: weighing 1g chitosan (CS) into a reaction bottle, adding 100mL of 1% acetic acid solution, heating at 40°C and stirring for 0.5h to dissolve to obtain solution A. Weighing 0.03mol GA into a reaction bottle, adding 10mL of 50% ethanol solution, stirring at 70°C for 1.0h to dissolve to obtain solution B. Weighing 5ml of 1.0mg / mL Fe 3+ Put it into a reaction bottle, add deionized water and ultrasonic, heat at 40℃ and stir for 0.3h to dissolve to obtain solution C. Mix solution A and solution B evenly and heat at 60℃, then mix them evenly with solution C and heat at 75℃, cool to room temperature, pour into a mold and dry to obtain a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film.

[0042] Example 6

[0043] A preparation method of a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film, comprising the following steps: weighing 1g chitosan (CS) into a reaction bottle, adding 100mL of 1% acetic acid solution, heating at 40°C and stirring for 0.5h to dissolve to obtain solution A. Weighing 0.03mol GA into a reaction bottle, adding 10mL of 50% ethanol solution, stirring at 70°C for 1.0h to dissolve to obtain solution B. Weighing 5ml of 1.5mg / mL Fe 3+ Put it into a reaction bottle, add deionized water and ultrasonic, heat at 40℃ and stir for 0.3h to dissolve to obtain solution C. Mix solution A and solution B evenly and heat at 60℃, then mix them evenly with solution C and heat at 75℃, cool to room temperature, pour into a mold and dry to obtain a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film.

[0044] Example 7

[0045] A preparation method of a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film, comprising the following steps: weighing 1g chitosan (CS) into a reaction bottle, adding 100mL of 1% acetic acid solution, heating at 40°C and stirring for 0.5h to dissolve to obtain solution A. Weighing 0.03mol GA into a reaction bottle, adding 10mL of 50% ethanol solution, stirring at 70°C for 1.0h to dissolve to obtain solution B. Weighing 5ml of 2.5mg / mLFe 3+ Put it into a reaction bottle, add deionized water and ultrasonic, heat at 40℃ and stir for 0.3h to dissolve to obtain solution C. Mix solution A and solution B evenly and heat at 60℃, then mix them evenly with solution C and heat at 75℃, cool to room temperature, pour into a mold and dry to obtain a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film.

[0046] Comparative Example 1

[0047] A method for preparing a pure chitosan film comprises the following steps: weighing 1g of chitosan (CS) and placing it in a reaction bottle, adding 100mL of 1% acetic acid solution, heating at 40°C and stirring for 0.5h to dissolve, mixing and stirring the above solution, heating at 75°C, cooling to room temperature, pouring into a mold and drying to obtain a pure chitosan film.

[0048] In Comparative Example 1, the film's mechanical properties and UV resistance are far from reaching the effects of Example 1.

[0049] In Examples 1-7 and Comparative Example 1, the present invention studies the effects of different addition amounts of gallic acid and ferric chloride on the film. In Example 6, when the addition amounts of gallic acid and ferric chloride are 0.3 mol / 100 mL and 1.5 mg / mL, respectively, the film has the best mechanical properties, antioxidant and anti-ultraviolet properties. Figure 2 From the scanning electron microscope (SEM) images, we can observe the microscopic morphology of a series of thin films. The surface of the pure CS film is relatively smooth, and its internal structure is mainly composed of numerous hydrogen bonds, forming a relatively uniform network. After the addition of gallic acid (GA), a unique ridge network cross-linking structure is formed due to the cross-linking between gallic acid molecules and chitosan polymer chains. When iron ions are added, the surface of the film presents a multi-network cross-linking structure, which is the result of the coordination interaction between iron ions and chitosan polymer chains and gallic acid molecules. Figure 3From the tensile test graph, we can observe the tensile properties of a series of films. The tensile strength of the chitosan composite film increases with the increase of gallic acid (GA) dosage. As the amount of iron ions increases, the tensile strength of the composite film further increases until the three reach the optimal ratio. When the amount of ferric chloride added continues to increase to 2.5 mg / mL (Example 7), the film-forming property of the prepared film is poor, and the mechanical strength is significantly reduced. Figure 4 The UV absorption test and light transmittance test show that with the increase of gallic acid addition, the UV absorption and light transmittance of CSGA composite film gradually increase. 3+ The addition of Fe further increased the UV absorbance and transmittance of the CSGA composite membrane. 3+ The addition ratio reaches 1.5mg / mL, which achieves the best comprehensive performance. Figure 5 As can be seen from the antioxidant test graph, fresh mango and apple slices were wrapped with the composite film prepared in Example 6 and placed at room temperature for 8 days. The decay degree of the samples on the 1st, 3rd, 6th and 8th days was observed. It can be seen that the freshness of the samples wrapped with the composite film was significantly better than that of the samples without any treatment. Figure 6 From the results of the hydrophobic angle test, it can be observed that the chitosan-based film has a certain hydrophobic effect. Figure 7 The UV resistance test paper test shows that the addition of Fe 3+ The chitosan film has a better UV protection effect.

[0050] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film, characterized in that: The following steps are involved: Step 1: Dissolve chitosan in acetic acid solution to obtain solution A; dissolve gallic acid in ethanol solution to obtain solution B; 3+ The salt is dissolved in deionized water to obtain solution C; Step 2: Mix solution A and solution B evenly and heat them, then mix them evenly with solution C and heat them, cool to room temperature, pour into a mold, and obtain a chitosan-based high-strength anti-ultraviolet and anti-oxidation composite film after drying.

2. The preparation method according to claim 1, characterized in that: In step 1, the concentration of chitosan in the solution A is 0.5-3 g / 100 mL, and the mass fraction of the acetic acid solution is 0.5-3%.

3. The preparation method according to claim 1, characterized in that: In step 1, the concentration of gallic acid in the solution B is 0.1-0.3 mol / 100 mL, and the mass fraction of the ethanol solution is 30%-80%.

4. The preparation method according to claim 1, characterized in that: In step 1, the Fe 3+ The concentration is 0.5-1.5mg / mL.

5. The preparation method according to claim 1, characterized in that: In step 1, the Fe 3+ The salt includes one or more combinations of FeCl3, Fe2(SO4)3, and Fe(NO3)3.

6. The preparation method according to claim 1, characterized in that: In step 2, the volume ratio of solution A, solution B and solution C is 20:2:

1.

7. The preparation method according to claim 1, characterized in that: In step 1, chitosan and acetic acid solution are mixed, heated to 30-50°C, and magnetically stirred for 0.2-0.8h until completely dissolved; gallic acid and ethanol solution are mixed, and magnetically stirred at 50-80°C for 0.5-1.5h until completely dissolved; Fe 3+ The salt was mixed with deionized water, ultrasonicated, and magnetically stirred at 30-50 °C for 0.1-0.5 h until completely dissolved.

8. The preparation method according to claim 1, characterized in that: In step 2, the solution A and solution B are mixed and then heated at 50-70° C., and the solution A, solution B and solution C are mixed and then heated at 60-85° C.